2021
DOI: 10.3390/ijerph18084165
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Incidence and Mortality of Skin Melanoma in Lithuania 1991–2015

Abstract: Background. We aimed to investigate age-specific and sex-specific incidence trends of melanoma in Lithuania from 1991 to 2015. Methods. Analysis was based on data from the population-based Lithuanian Cancer Registry database for 1991–2015, and 6024 cases of skin melanoma were identified. Age-adjusted rates (ASRs) by sex and age group were calculated. Adjustment for ASRs was done using the old European standard population, where a total of three age groups were considered: 0–39, 40–59 and 60+. Additionally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…A statistically significant increase in the incidence of melanoma was reported, with an average annual change of 4% in males and 3% in females between 1995 and 2012 in Europe [ 4 ]. A similar trend was observed in Lithuania, where the overall melanoma rates increased annually by (APC) 3.9% in males and 2.3% in females; the highest incidence of melanoma was noticed in 60 years and older adult group of both sexes, while the lowest incidence was in a group of 39 years and younger adults [ 5 ].…”
Section: Introductionsupporting
confidence: 73%
“…A statistically significant increase in the incidence of melanoma was reported, with an average annual change of 4% in males and 3% in females between 1995 and 2012 in Europe [ 4 ]. A similar trend was observed in Lithuania, where the overall melanoma rates increased annually by (APC) 3.9% in males and 2.3% in females; the highest incidence of melanoma was noticed in 60 years and older adult group of both sexes, while the lowest incidence was in a group of 39 years and younger adults [ 5 ].…”
Section: Introductionsupporting
confidence: 73%
“…Different patterns in incidence rates depending on latitude and north-south gradients have been observed in several countries and world regions. Although melanoma rates continue to increase in most European countries, rates in North America and Oceania appeared to have leveled off in recent years . Temporal variations in melanoma incidence in high-risk populations are associated with a strong cohort effect, with rates stabilizing or decreasing among recent generations in some countries .…”
Section: Discussionmentioning
confidence: 99%
“…Although melanoma rates continue to increase in most European countries, rates in North America and Oceania appeared to have leveled off in recent years. 1,2,7,8,22 Temporal variations in melanoma incidence in high-risk populations are associated with a strong cohort effect, with rates stabilizing or decreasing among recent generations in some countries. 1 In Australia, the country with the highest melanoma incidence rates worldwide, more than 95% of all melanoma cases have been attributed to high ambient levels of UV radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence in children aged 10–19 in the United States also decreased from 2000 to 2015 [ 207 ]. In Eastern Europe, studies from Lithuania (1991–2015) and Ukraine (2002–2013) reported increased incidence of melanoma in all age groups [ 208 , 209 ], but there is evidence of a recent decline in incidence in Hungary [ 210 ].…”
Section: Human Healthmentioning
confidence: 99%